2017
DOI: 10.5935/1518-0557.20170009
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality before cryopreservation and after thawing in 543 patients with testicular cancer

Abstract: ObjectiveThe main objective of this study was to assess semen characteristics of patients with testicular cancer before cryopreservation and after thawing, to evaluate the consequences of this technique on sperm quality in patients with testicular cancer.MethodsFive hundred eighty-nine samples from 543 patients with testicular cancer were cryopreserved between 1995 and 2015, one aliquot per patient was used for a thawing test to assess the impact of cryopreservation on sperm motility; semen analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…Sperm motility is known as one of the vital parameters to assess male fertility and essential for natural conception. Patients with testicular cancer have been reported with subnormal sperm motility (asthenozoospermic) (Agarwal et al ., ; MacKenna et al ., ; Hamano et al ., ). These patients require ART procedures such as IUI or IVF to establish pregnancy.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Sperm motility is known as one of the vital parameters to assess male fertility and essential for natural conception. Patients with testicular cancer have been reported with subnormal sperm motility (asthenozoospermic) (Agarwal et al ., ; MacKenna et al ., ; Hamano et al ., ). These patients require ART procedures such as IUI or IVF to establish pregnancy.…”
Section: Discussionmentioning
confidence: 96%
“…Poor semen quality with reduced fertilization rates is well reported in testicular cancer patients (Hallak et al ., ; Gandini et al ., ; Ping et al ., ; Auger et al ., ). Sperm motility in these patients is reduced and below the WHO reference values of >40% (Djaladat et al ., ; Záková et al ., ; MacKenna et al ., ; Hamano et al ., ).…”
Section: Introductionmentioning
confidence: 96%
“…Critser et al demonstrated apoptosis and motility loss in up to 50–75% of frozen-thawed spermatozoa (Critser et al , 1988). A more recent study has demonstrated a decrease in TMSC by 32% (Mackenna et al , 2017). Interestingly, the cryosensitivity of motility was significantly higher in the healthy transwomen specimens.…”
Section: Discussionmentioning
confidence: 99%
“…While the spermatotoxic potential of cancer treatments such as chemotherapy and radiation therapy is well recognized, the effect of malignancy itself on male fertility prior to oncologic treatment is less clearly understood. It has been suggested that as many as two-thirds of cancer patients have impaired fertility at baseline (van Casteren et al, 2010), but studies have reported heterogeneous findings as to whether and how specific types of malignancy are linked to diminished semen parameters (Auger et al, 2016;Caponecchia et al, 2016;Paoli et al, 2016;DiNofia et al, 2017;MacKenna et al, 2017). This study investigated whether sperm bankers with various forms of malignancy demonstrated worse baseline semen parameters as compared to individuals with non-oncologic indications for banking.…”
Section: Introductionmentioning
confidence: 98%
“…It has been suggested that as many as two-thirds of cancer patients have impaired fertility at baseline (van Casteren et al, 2010), but studies have reported heterogeneous findings as to whether and how specific types of malignancy are linked to diminished semen parameters (Auger et al, 2016;Caponecchia et al, 2016;Paoli et al, 2016;DiNofia et al, 2017;MacKenna et al, 2017). It has been suggested that as many as two-thirds of cancer patients have impaired fertility at baseline (van Casteren et al, 2010), but studies have reported heterogeneous findings as to whether and how specific types of malignancy are linked to diminished semen parameters (Auger et al, 2016;Caponecchia et al, 2016;Paoli et al, 2016;DiNofia et al, 2017;MacKenna et al, 2017).…”
Section: Introductionmentioning
confidence: 99%